Social capital in the urban informal sector in developing countries: Micro evidence from small textile producers in Bolivia - Kurt Annen (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2006)
In a setting with a low level of anonymous trust and without an effective shadow of courts, the possibility to return a low quality good can work as a simple mechanism to overcome moral hazard in buyer seller transactions. Informal firms – in contrast to formal ones – operate in the hidden and do not use receipts for their transactions. They appear on informal markets on a more or less frequent basis. These factors make it difficult for buyers to return a good unless there is a social link between the seller and the buyer. According to this idea, social trust relationships increase sales for informal firms but not for formal ones. Furthermore, formal firms have more sales than informal ones when controlling for the level of social capital of informal firms. The paper uses micro-level data obtained from surveying small textile producers in Bolivia to test these predictions. The results show that family relationships and trust relationships substantially increase sales for informal firms but not for formal ones. Furthermore, informal firms without social capital earn substantially less than formal firms.
Keywords: 330; Social Capital; Anonymous Trust; Informal Sector; Small Firms; Social Capital; Informeller Sektor; Ballungsraum; KMU; Textilhandwerk; Bolivien